Tantangan dan Peluang dalam Implementasi Kebijakan Lingkungan di Pemerintahan Daerah - Riduan, Akhmad (Bulletin of Community Engagement, 2024)
Implementation of environmental policies in local government faces various complex challenges. One of the main challenges is limited resources, both in terms of finance and competent human resources. Many local governments have difficulty providing adequate budgets for environmental programs due to competing priorities with other sectors such as infrastructure and health. Apart from that, the lack of experts in the environmental field also worsens this situation, hampering the effectiveness of implementing the policies that have been formulated. On the other hand, regulatory challenges and coordination between institutions also pose significant obstacles. Regulations that are not in sync between the central and regional governments often cause confusion in implementing policies in the field. Poor coordination between government institutions, both horizontally and vertically, also causes overlapping programs and ineffective policies. This condition is exacerbated by the low level of public participation in the process of making and implementing policies, which causes a lack of support from the community. However, there are great opportunities in efforts to implement environmental policies that can be optimized by local governments. The use of technology and innovation in environmental management, such as geospatial information systems and real-time air quality monitoring, can increase the efficiency and effectiveness of environmental programs. In addition, partnerships with the private sector and non-government organizations can also be a catalyst in strengthening capacity and financing. The existence of global awareness about the importance of environmental sustainability also opens up opportunities for local governments to obtain international support in the form of funds and technical for environmental projects. Keywords: Limited Resources, Synchronized Regulations, Innovative Technology, Strategic Partnerships